SELF-CONTROL FORMATION TECHNOLOGY FOR PRIMARY SCHOOL CHILDREN WITH MILD MENTAL RETARDATION IN LEARNING PROCESS - Vera A. Galkina (Russian State Vocational Pedagogical University, 2015)
The purpose of the article is to present self-control development technology meeting up-to-date requirements in the special education for pupils with mild mental retardation; to reveal the self-control special features for children of the studied category found during the experiment; to show necessity of the task-oriented work. Methods. The methods involve theoretical analysis of relevant psychologicpedagogical and methodical literature; empiric methods (conversation, writing tasks, observation); pedagogic experiment; quantitative and qualitative analysis. Results. The article contains the data obtained during the experiment concerning study of the self-control special features for primary school children with mild mental retardation in learning process. The author describes and scientifically justifies the self-control development technology based on the step-bystep approach for children of the studied category. The revealed reasons of low self-control level for primary school children with intellectual disorder are proven by qualitative and quantitative analysis. The presented experimental results confirm the developed technology efficiency and can be applied while studying of all disciplines at primary school. Scientific novelty. For the first time the unified (may be used at all subjects) and comprehensive (for all self-control components) self-control development technology was developed and proven for primary school children with mild mental disorder in learning process; transient phase necessity is proved and justified for mastering all control kinds by primary school children with mild mental retardation. Practical significance. The developed technology allows qualitative enhancement of learning activities for primary school children with mild mental retardation. The research results may be used in both correctional and educational work at special (correctional) schools (type VIII) and at general-education schools. In addition the results may be useful in training of primary school teachers and students.